Substratos e recipientes na produção de Porta-enxertos de Cajueiro - Castro, Nailton Rodrigues de (2019)
The use of alternative substrates in the production of rootstocks of dwarf-early cashew is important as an interesting option for Nurserers, aiming mainly at reducing the use of chemical fertilizers and commercial substrates, expanding the autonomy Of seedling producers and conferring new uses for the residues available in the region, in addition to reducing the environmental impact in their production, since they are composed of residues.Thus, this study aimed to compare alternative substrates, free of soil and the basis of organic municipal and agroindustrial residues, with commercial substrates for the production of dwarf cashew seedlings, in two types of containers. The treatments were distributed in randomized blocks, in the factorial scheme (5 x 2), being 5 substrates [(substrate 1: sewage sludge, manure of pure laying hen (3:1) and plaster (50 kg M-3); Substrate 2: Green coconut fiber, sewage sludge, pure laying hen manure (3:1:1) and plaster (50 kg M-3); Substrate 3: Green coconut fiber, pure laying hen manure (3:1) and plaster (50 kg M-3); Substrate 4: Substrate used by a local nurseririst consisting of sandy surface land and black hydromorphic Land (2:1); Substrate 5: Commercial substrate Germina Plant Horta®)] and 2 containers (tubete and plastic bag), with 3 replications. The variables analyzed were: Germination rate, number of seedlings able for grafting, height of aerial part (cm), stem diameter (mm), number of leaves/plant, length of main root (cm), dry mass of aerial part and Root system (g), quality Of the seedling, chlorophyll content, gaseous exchanges: CO2 assimilation rate (A, μmol CO2 m-2 S-1), stomatal conductance (GS, mol M-2 S-1), transpiration rate (E, mmol water vapor m-2 S-1), internal CO2 concentration (Ci), ratio between internal concentrations and CO2Environment (Ci/Ca), intrinsic (A/GS) and instantaneous (A/E) efficiencies of water use and instantaneous carboxylation efficiency (A/Ci). The size of the container influenced the development of the rootstock, being more recommended the use of plastic bags and the commercial substrate is more recommended for seedling production, due to the substrates the base of sludge present a high conductivity And the substrate of the nurseririst present a low amount of nutrients.